Students' Thriving and Well-Being in Online Learning Environments in Vocational Education and Training - Kiikeri, Pia; Uusiautti, Satu; Purtilo-Nieminen, Sirpa (International Journal for Research in Vocational Education and Training, 2024)
Context: Recent research on students' experiences with the quality of online learning during the COVID-19 pandemic has increased the challenge to the development of online learning. During the pandemic, anxiety, depression, and fatigue occurred in online studies, which also weakened students' well-being. In this quantitative study, we examined how students thrive in synchronous and asynchronous online implementations. The goal of the research was to support students' well-being in online studies; therefore, the study uses the PERMA well-being theory. Approach: Finnish vocational education and training students (N = 363) participated in the study and answered the questions on positive emotions, engagement, relationships, meaning, and accomplishment from both asynchronous and synchronous online delivery perspectives using a questionnaire. Findings: This study highlighted the importance of the teacher's online learning facilitation skills and task design skills, and the emotions generated in an online course. Based on the results, the respondents were divided into three student profiles: (1) Students thriving in online courses in general; (2) Students thriving, especially in asynchronous online courses; and (3) Students not thriving in online courses in general. Conclusions: According to the findings, students need different options for completing online courses. The role of the teacher in creating a positive and supportive atmosphere, fostering relationships, and creating clear work-related and versatile tasks is of great importance in the generation of emotions, whether it is an asynchronous or synchronous online implementation.